Self-Control and Risky Sexual Behavior Teenager - Thien, Alesandro Delvicchio; Littik, Serlie; Wijaya, R. Pasifikus Ch. (Universitas Nusa Cendana, 2023)
Late adolescence as the next generation of the nation must have a good mentality and behavior to become the next generation. However, in reality, many adolescents have reproductive health problems, such as abortion, HIV/AIDS, STDs, and pregnancies outside of marriage, which are caused by adolescents' misunderstanding of sexuality and freedom of sex. The purpose of this study was to determine the correlation between self-control and risky sexual behavior in late adolescents in Kupang City. The number of samples in this study were 380 late adolescents in the city of Kupang, male and female. Collecting data in this study used a scale of self-control and a scale of risky sexual behavior, and was taken using a purposive sampling technique. Test the h ypothesis using correlation statistical techniques, the results of the correlation coefficient value are - 0.829 with a significant number of Sig. < 0.05. This means that there is a significant negative correlation between self-control and risky sexual behavior in late adolescents in Kupang City. The higher the self-control, the low-risk sexual behavior, conversely, if the self-control is low, the risky sexual behavior is classified as high